Serum zinc level in Nigerian children with febrile convulsion - Okposio, Matthias M.; Sadoh, Wilson E.; Ofovwe, Gabriel E.; Onyiriuka, Alphonsus N. (Journal of Pediatric Neurology, 2012)
Febrile convulsion is one of the most common childhood neurological disorders. The underlying mechanism remains unclear; however, some reports have suggested that low serum zinc levels may be implicated in its pathogenesis. This case-control study was carried out to determine the serum zinc levels in Nigerian children with febrile convulsions in comparison with matched febrile controls without convulsions. Ninety children with febrile convulsions and 90 matched febrile children without convulsions were recruited. Serum zinc was measured using Atomic absorption spectrophotometer (Perkin-Elmer 306 USA). The data was analyzed with SPSS version 16 statistical package and student t-test was employed to compare mean serum zinc between the two groups. The mean serum zinc level of children with febrile convulsion (58.7 ± 25.4 μg/dL) was significantly lower than that of febrile controls (90.3 ± 33.0 μg/dL), (P < 0.0001). Hypozincemia may indeed play a role in the occurrence of febrile convulsion.
Keywords: Zinc; febrile convulsion; Nigerian; children